Perancangan Aplikasi Keamanan Pesan Teks dengan menggunakan Algoritma Triple Transposition Vigenere Cipher - Fauzi, Muhammad Anas (MEANS (Media Informasi Analisa dan Sistem), 2019)
Security is a very important aspect of information systems. Some information is generally only intended for a certain group of people, therefore security is needed to prevent the information from reaching other parties who are not interested so that the possibility of leakage or misuse of information can be avoided by designing a security system that serves to protect the information system . Information security issues that we often encounter include passive tapping, active tapping, fraud and so on. In addition there are two main problems of text message security that must be considered by the user, namely the problem of privacy (privacy) and authenticity (autenthication). To overcome the above problems, the writer tries to design an application that can be used to do the encryption and decryption process by applying the triple transposition vigenere cipher algorithm in encryption and decryption. This algorithm is a super encryption algorithm, because in the encryption process it uses two techniques, namely transposition technique and substitution technique. The substitution technique in this algorithm uses the vigenere cipher algorithm.